A comparative analysis of the impact of climate change on emergence of infectious diseases and outbreaks in remote areas of Sindh, Pakistan - Miss Hafsa Faruqui; Dr. Saeed Khan (International Journal of Infectious Diseases)
Introduction: Remote areas in the Sindh province of Pakistan are characterized by challenging terrain, limited access to healthcare, and poor infrastructure. These regions often face a higher burden of infectious diseases due to the lack of proper healthcare facilities. Diagnostic surveillance plays a crucial role in monitoring disease prevalence since it enables early detection, timely intervention, and developing effective public health strategies. Among other factors, climate change also influences disease distribution and severely impacts the incidence of several illnesses. For instance, recent flooding in Sindh caused a surge in waterborne diseases, due to contaminated water sources and inadequate sanitation that act as breeding grounds for pathogens. Comparative analysis of disease surveillance pre- and post-floods can help in understanding the changes in disease dynamics which are instrumental in refining public health strategies and optimizing resource allocation in the face of environmental challenges. This study was designed to compare and analyze disease distribution before and after the 2022 floods in remote areas of Sindh, Pakistan. By comparing the two time periods, the study aimed to identify seasonal trends for infectious diseases to design effective strategies that minimize transmission rates and reduce healthcare burden. Methods: To access the rough terrain in the remote areas of Sindh, a USAID funded, fully-equipped BSL-2 mobile laboratory with a team of microbiologists from the Provincial Public Health Laboratory, Dow University of Health Sciences visited Ratodero, Aarija Taluka, Kambar, Nasirabad, Dokery, Sukkur, and Gadap. This study happened in two phases, before and after the 2022 floods. Diagnostic tests for HIV, malaria, hepatitis B, hepatitis C, typhoid, and COVID-19 antibody were performed, along with complete blood count. Results: A total of 2858 tests were performed out of which 56% were males and 44% females. During phase I (pre-floods), 5.2% had malaria, 1.9% had HCV, and 12% were positive for COVID-19 antibody. During phase II (post-floods), 46.6% were positive for malaria, 31.7% for COVID-19 antibody, 9.2% for HCV, 8% COVID-19 antigen, and few cases of HIV, hepatitis B, and typhoid were also detected. Discussion: This study highlights the pressing health challenges faced by remote areas in Sindh, Pakistan, exacerbated by climate change-induced events like floods. The comparative analysis of disease distribution before and after the 2022 floods underscores the vulnerability of these regions to infectious diseases like malaria and COVID-19. Conclusion: Climate change poses a significant threat to low-income countries, especially remote areas, worsening the already considerable disease burden they face. Routine monitoring and surveillance of disease prevalence is crucial to create targeted interventions that bridge the gap in these vulnerable regions and lessen the burden on the healthcare systems.